EFFECT OF COMPONENT APPLICATION OF ORGANIC AND BIOLOGICAL FERTILIZERS ON HEAVY METALS AND PESTICIDE RESIDUES IN SOIL (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The use of biological preparations against the background of organic fertilizers (green manure and manure) provides a reduction in the amount of heavy metals in the mobile form in the soil compared to the background (control) agrocenosis N250P175K125. Organic fertilizers improve the ecological condition of the soil and increase the amount of humus, as a result of which heavy metals entering the soil are adsorbed by organic substances, at the same time residues of pesticides such as HCH and DDT are reduced, and the ecological stability of the soil is ensured.